Recorded behaviours by GoPro of anemonefish species Amphiprion clarkii and Amphiprion melanopus in observer presence and observer absence, Vanuatu, 2019 - Trnski, Lena (PANGAEA, 2020)
Anemonefish species are iconic tropical reef fish which occur in many recreational tourism hotspots. They tend to be highly territorial of their host anemone and display many behaviours relating to their purpose in defending it. Territorial behaviours of two anemonefish species (Amphiprion clarkii and Amphiprion melanopus) were observed in six anemones via snorkeler observation, stimulating observer presence. A GoPro was used to record behaviours in the absence of humans. Other factors including tourism level (0; no tourism - 8; high tourism), the number of fish in the anemone, anemone species, anemone depth (by dive computer) and fish size (by visual approximation) were also measured to examine in relation to fish behaviours. Data was collected off the coast of Efate island in Vanuatu (17° 44' 5'' S, 168° 19' 19'' E) from 5 to 26 January, 2019. For each sample, two anemones at least 20 metres apart (either Entacmaea quadricolor or Heteractis crispa) were selected. At each anemone, a GoPro camera was set up with a view of the entire anemone. At anemone 1, observer presence was simulated by hovering 1-3 metres over the anemone. The GoPro recorded anemonefish behaviours at anemone 2 in the absence of observers. The first 2 minutes of GoPro footage was disregarded from observer absence recordings to reduce possible influence of deployment. The subsequent 15 minutes were used for observation from both anemones. Behaviours of all anemonefish in both anemones were observed. In total, 21 fish were sampled from six anemones. For each individual fish, a single behaviour was recorded every 15 seconds for 15 minutes, resulting in 60 behavioural events. This was done for each fish individual twice: once in observer presence, once in observer absence. The values in the behaviour variable is the number of times each fish individual completed the behaviours of watching, hiding, roaming, inter- or intraspecific competition out of 60.
Keywords: Anemonefish; Behaviour; Boldness; Intraspecific competition; Observer bias; Vanuatu